Analysis of the Influence of Household Organic Waste Management through the Utilization of Eco Enzyme and Public Awareness of Environmental Impacts - Sucianti Sukiana Sari; Samsul Bahri; Albar Albar (Journal of Public Representative and Society Provision, 2026)
The purpose of this study is to examine how waste management practices and environmental impact are affected in Wonomulyo District, Polewali Mandar Regency, by the use of eco-enzymes and organic waste management.  The large amount of organic waste produced in conventional markets and the general lack of knowledge about environmental effects serve as the foundation for the study.  Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 was used in a quantitative manner.  Structured questionnaires addressing eco-enzyme, organic waste, environmental impact, and waste management factors were used to gather data from household respondents.  The findings demonstrate that eco-enzyme, like organic waste management, has a favorable and noteworthy impact on waste management and environmental impact.  The relationship between eco-enzyme and waste management, as well as between organic waste and waste management, is mediated by environmental impact, which also has a major impact on waste management.  In order to achieve efficient and sustainable waste management, these findings emphasize the significance of combining community-based appropriate technology with increased environmental consciousness.  The study's conclusions can be used as a foundation for developing regional regulations pertaining to the control of organic waste and the mitigation of climate change.